2015
DOI: 10.1016/j.healthplace.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic context and change in allostatic load among older Puerto Ricans: The Boston Puerto Rican health study

Abstract: Neighborhood context may influence health and health disparities. However, most studies have been constrained by cross-sectional designs that limit causal inference due to failing to establish temporal order of exposure and disease. We tested the impact of baseline neighborhood context (neighborhood socioeconomic status factor at the block-group level, and relative income of individuals compared to their neighbors) on allostatic load two years later. We leveraged data from the Boston Puerto Rican Health Study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 50 publications
0
39
1
Order By: Relevance
“…The literature search yielded 14 eligible papers [ 10 , 16 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], published from 2009 to 2016. Detailed information on their main characteristics can be found in the Supplementary Table 1 ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search yielded 14 eligible papers [ 10 , 16 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], published from 2009 to 2016. Detailed information on their main characteristics can be found in the Supplementary Table 1 ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean sample size was 3068 participants, ranging between 420 [ 31 ] and 13,199 [ 26 ]. Twelve out of the 14 studies used adult samples [ 16 , 26 , 27 , 28 , 29 , 30 , 32 , 34 , 35 , 36 , 37 , 38 ] and two focused on youth [ 31 , 33 ]. Seven studies included participants of different races/ethnicities [ 16 , 26 , 27 , 28 , 29 , 30 , 38 ], four studies exclusively focused on Blacks [ 31 , 33 , 35 , 36 ], and one on Hispanics [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…One mechanism potentially linking socioeconomic status (SES) and health is the psychoneuroendocrine pathway and the involvement of stress-related cortisol responses ( Lupien et al, 2001 ). A body of research has suggested a link between lower income and higher salivary and urinary cortisol levels ( Dowd et al, 2009 , Jimenez et al, 2015 ). Lower income and education have also been associated with elevated diurnal cortisol values and with flatter diurnal rhythms in a graded fashion ( Cohen et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…tionships of allostatic load with morbidity and mortality risk, an inverse relationship between SES and allostatic load has been observed across multiple samples(Crimmins et al, 2009;Dowd et al, 2009;Jim enez, Osypuk, Arevalo, Tucker, & Falcon, 2015;Robertson et al, 2014;Seeman, Crimmins, et al, 2004;Seeman et al, 2010Seeman et al, , 2014Szanton et al, 2005;Upchurch, Rainisch, et al, 2015;Upchurch, Stein, et al, 2015). Educational attainment, an indicator of SES, also is significantly inversely related to allostatic load(Barboza Solís et al, 2015;Gale et al, 2015;Hansen et al, 2016;Kubzansky et al, 1999;Lipowicz et al, 2014; Petrovic et al, 2016;Rosenberg et al, 2014;Robertson & Watts, 2016;Seeman, Crimmins, et al, 2004;Seeman et al, 2008;Upchurch, Rainisch, et al, 2015;Upchurch, Stein, et al, 2015;Weinstein et al, 2003;Zilioli et al, 2015).…”
mentioning
confidence: 98%